2004
DOI: 10.3748/wjg.v10.i5.725
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between inducible nitric oxide synthase expression and angiogenesis in primary gallbladder carcinoma tissue

Abstract: Angiogenesis of PGBC is significantly related to the biological behaviors of PGBC. The expression of iNOS is related to the biological behaviors of PGBC. The detection of MVD and the expression of iNOS in PGBC can be used as parameters to determine the degree of malignancy and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…Kong [6,9,16,21,22,27]. Conversely, Ropponen et al and Puhakka et al reported that patients with tumors showing high expressions of iNOS and other NOS izozymes had better survival rates in colorectal and non-small cell lung carcinomas [25,29].…”
Section: Discussionmentioning
confidence: 98%
“…Kong [6,9,16,21,22,27]. Conversely, Ropponen et al and Puhakka et al reported that patients with tumors showing high expressions of iNOS and other NOS izozymes had better survival rates in colorectal and non-small cell lung carcinomas [25,29].…”
Section: Discussionmentioning
confidence: 98%
“…[24] Analysis of the relationship between angiogenesis and iNOS in primary gallbladder carcinomas has shown that the degree of malignancy is significantly affiliated with the expression level of iNOS. [25] In breast cancer, NO • is shown to decrease aggressiveness of breast tumor cells by inhibiting cell motility and reinforcing cell adhesion, ultimately hindering the cell’s metastatic characteristics. [26] While NO • has been clinically connected to a poor cancer prognosis, not all the effects of NO • are clear and may be impacted by dose or organs involved.…”
Section: Introductionmentioning
confidence: 99%
“…Inducible nitric oxide synthase expression has been detected immunohistochemically in the human GB with acute cholecystitis or GB tumors. Few reports have been published on iNOS expression in normal GB tissue and, in pathological conditions, previous studies have focused on epithelial cells 14–16 …”
Section: Introductionmentioning
confidence: 99%